Kami Berhasil Bertahan Meski Belajar Online (Pandemi covid-19) - Fatma Nuraqmarina; Winy Nila Wisudawati (Neolectura, 2023)
According to the results of the Survey of Home Learning performed by the Directorate General of Higher Education of the Ministry of Education and Culture regarding online lectures during the epidemic, most students believe that online lectures are ineffective. The goal of this study was to see if there was a difference in the grit of students from State Universities (PTN) and Private Higher Education (PTS) during Online Learning during the Covid-19 Pandemic. This study's population consisted of PTN and PTS students. While the samples in this study were students of PTN and PTS in Jakarta. This survey included 62 students from public universities and 62 from private universities. Angela L Duckworth produced a grit scale questionnaire with 12 components, which was used to collect data. The two-group difference test was employed in the data analysis procedure to compare the grit of PTN and PTS students. In this study, there was a significant difference in grit between students at state universities (M = 39.0484, SD = 5.87974) and students at private colleges (M = 42.0806, SD = 7.82870), t = -2.439, p = 0.016. The mean grit of public college students is lower than that of private university students.